PERANCANGAN FILM PENDEK TENTANG KETAPEL BERJUDUL “STORY OF KETAPEL” - Renaldo Rolina (Jurnal Titik Imaji, 2021)
Slingshot is one of  may traditional games. Traditional games are recreational activities that have certain rules as a reflection of the nation. In this case, the catapult is one of the traditional games that has the potenial to show its cultural authenticity. than one of the media that is considered capable of sharing information about this catapult is a short film. In this design, the author uses qualitative method with techniques to collect data through field observation, questionnaires, literature studies and interviews. The author made a direct visit to the place where the catapult was made. Questionnaires were distributed to 158 people online on social media and the library funcioned to find data that could support the topic of the problems raised. In this study, the results of 158 questionnaires distributed stated that almost all respondents did not know how to play and make a slingshot. However, through the questionnaire it was also found that the community still has a high interest in catapults. So to solve the problem, the author make a short film telling about catapults that lead to teenagers and the community.The conclusion of this design is to provide information and direction to teenagers 17-25 years old to be able to learn to understand, love and preserve the traditional game of slingshot.